Investigating Effect of Soluble Sodium Sulphate Contamination on Swell Behaviour of Untreated and Lime-Treated Soil - Shivanshi; Jha, Arvind Kumar; Akhtar, Mohammad Parwez (Indian Geotechnical Journal, 2023)
Deterioration of expansive clayey soil upon lime treatment subjected to sulphate attack has acquired sincere attention. The announcement of heave or swell in the presence of sulphate contamination affects the stability of ground. It is evidenced that reactions between lime, soil and sulphate induces swell due to the generation of expansive ettringite compound, thereby causing sever distresses. Ettringite formation, its growth, factors affecting and swell behaviour have not been thoroughly understood yet and hence needed to be explored. Explicating the influence of extent of sulphate content on lime-stabilized soil is still a subject of current research. The present investigation is carried out to elucidate the effect of varying concentrations (0, 1000, 3000, 5000, 8000, 10,000, 16,000, 20,000 and 30,000 ppm) of sodium sulphate ( Na 2 SO 4 ) solutions on swell behaviour [free swell index and swell percentage] and physicochemical characteristics [pH and electrical conductivity]. It is revealed that lime-treated soil is found to be more sensitive and vulnerable in the presence of sodium sulphate contamination. The maximal swell or ultimate heave is produced at a concentration of 10,000 ppm and beyond that swell percentage of treated soil is reduced due to the predominant effect of cementitious compounds over ettringite. Additionally, higher sulphatic concentration exhibited deleterious consequences due to emerged growth of ettringite. The variations appeared at varying sodium sulphate contents are expounded through microanalyses (XRD, FESEM, EDAX, FTIR and TGA-DTA). The results comprehended that sulphate concentrations play an eminent role in announcing the development of ettringite, thus leading to baneful impacts on swell behaviour.